Long-Term Outcomes of Longitudinal Efficacy Study With Tolvaptan in ADPKD - Eiji Higashihara; Kikuo Nutahara; Masayuki Itoh; Takatsugu Okegawa; Mistuhiro Tambo; Tsuyoshi Yamaguchi; Yu Nakamura; Satoru Taguchi; Shinya Kaname; Kenichi Yokoyama; Tatsuya Yoshioka; Hiroshi Fukuhara (Kidney International Reports, 2022)
Introduction: The effects of long-term and uninterrupted tolvaptan treatment on autosomal dominant polycystic kidney disease (ADPKD) are unclear. Therefore, a more than 3-year continuous treatment study was performed. Methods: From the Kyorin University cohort, 299 patients were surveyed and 179 patients were indicated for tolvaptan having a total kidney volume (TKV) ≥750 ml, TKV slope ≥5%/yr, and estimated glomerular filtration rate (eGFR) ≥15 ml/min per 1.73 m2. Among 179 patients, 118 patients consented to the study. Results: Retrospective pretreatment and prospective on-treatment periods had a median of 1.8 and 4.0 years, respectively. During the 5 treatment-years, the log10(TKV) slope/yr decreased from the pretreatment period (P < 0.0001) and the estimated height-adjusted TKV growth rate α (eHTKV-α, %/yr) decreased from baseline (P < 0.0001). The decline in eGFR improved in female patients (P < 0.0001), but not in males (P = 0.6321). Furthermore, during the 5 treatment-years, eGFR remained significantly better in the group with a percent decrease in eHTKV-α from baseline to the first treatment-year ≥ the median (2.94%) than in the group with a decrease <2.94%. The free-water clearance was higher in males than in females irrespective of treatment. Conclusion: The TKV growth rate decreased in 4 years with tolvaptan in both sexes. The insignificant effects of tolvaptan on the eGFR slope in males were likely due to androgen stimulation of cystogenesis and analytical difficulty of longitudinal changes in nonlinear trajectories of eGFR. The larger decrease in eHTKV-α in the first year was related to a better renal prognosis. The vasopressin-mediated water reabsorption was activated more in females than males irrespective of tolvaptan administration.